Editorial. (May 2013) - Tim, Schadla-Hall; Larkin, Jamie; Thornton, Amara
<x content-type="archive" xml:space="preserve">Abstract</x> Future historians, pondering changes in British society from the 1980s onwards, will struggle to account for the following curious fact. Although British business enterprises have an extremely mixed record (frequently posting gigantic losses, mostly failing to match overseas competitors, scarcely benefitting the weaker groups in society), and although such arm's length public institutions as museums and galleries, the BBC and the universities have by and large a very good record (universally acknowledged creativity, streets ahead of most of their international peers, positive forces for human development and social cohesion), nonetheless, over the past three decades politicians have repeatedly attempted to force the second set of institutions to change so that they more closely resemble the first. (Collini, 2013: 12)